2014
DOI: 10.5657/fas.2014.0361
|View full text |Cite
|
Sign up to set email alerts
|

Target Strength Measurements of Live Golden Cuttlefish Sepia esculenta at 70 and 120 kHz

Abstract: Cuttlefish Sepia esculenta are commercially important in Korea. Assessments of their biomass currently depend on fishery-landings data, which may be biased. Towards fishery-independent acoustic surveys of cuttlefish, target strength (TS) measurements at 70 and 120 kHz were made of 23 live cuttlefish, in early May 2010. The fish were caught by traps in the inshore waters around Geojedo, Korea. The TS were measured using split-beam echosounders (Simrad ES60 and EY500, respectively). The cuttlefish mantle lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…These characteristics-such as length, weight, width and thickness-were measured following completion of the acoustic experiments. The mean tilt angles (<θ>) with standard deviations (S θ ) measured for 19 live cuttlefish at 70 and 120 kHz in our earlier study (Lee and Demer 2014) are shown in Table 2. The TS and θ for these live cuttlefish were measured simultaneously using a split-beam echo sounder and a CCTV camera system, respectively and the (<θ>) and S θ values were used in estimating the tilt-averaged TS from the TS functions of the corresponding cuttlebone.…”
Section: Specimens and Measurement Of Target Strengthmentioning
confidence: 99%
See 4 more Smart Citations
“…These characteristics-such as length, weight, width and thickness-were measured following completion of the acoustic experiments. The mean tilt angles (<θ>) with standard deviations (S θ ) measured for 19 live cuttlefish at 70 and 120 kHz in our earlier study (Lee and Demer 2014) are shown in Table 2. The TS and θ for these live cuttlefish were measured simultaneously using a split-beam echo sounder and a CCTV camera system, respectively and the (<θ>) and S θ values were used in estimating the tilt-averaged TS from the TS functions of the corresponding cuttlebone.…”
Section: Specimens and Measurement Of Target Strengthmentioning
confidence: 99%
“…The biological and morphological characteristics of 19 specimens of cuttlebone and the corresponding live cuttlefish (Lee and Demer 2014) used in the TS experiments are shown in Table 1. These characteristics-such as length, weight, width and thickness-were measured following completion of the acoustic experiments.…”
Section: Specimens and Measurement Of Target Strengthmentioning
confidence: 99%
See 3 more Smart Citations